The Use of Slang Language as Strategy of Communication in Alasrajah Village: A Sociolinguistic Study - Tri Pujiati; Rosiana Sukma Anjani; Dede Rosyadi ZA; Bima Kurniawan (Universitas Islam Negeri Palopo, 2025)
Language acts as the main means of communication and self-identity, which continues to develop along with social, cultural, and technological changes. Among teenagers, slang is an important part of informal communication, enabling the formation of group identity and solidarity. The use of slang language among teenagers in Alasrajah Village, Bangkalan Regency are very unique. This study tries to analyze the use of slang language by exploring the forms, functions, and social and cultural factors that play a role in its formation. This research uses a descriptive qualitative method by applying a sociolinguistic approach. This research was conducted in Alasrajah Village, Bangkalan, Madura, East Java on 2024. The results of the study identified five main types of slang: (1) fresh and creative slang at about 38,48%, clipping at about 15, 38%, compounding 15, 38%, acronym 15, 38%, and imitative 15, 38%. Each of which has its own social and communicative functions. Moreover, the use of slang in Alasrajah strengthens the social identity, facilitates informal communication, and expresses resistance to formal language rules. The main factors in the formation of this slang language are the influence of social media and local dialects, which together create a linguistic expression that is distinctive and rooted in cultural identity. This study provides insight into how language functions as a means of communication and a reflection of the social dynamics that develop in local communities.